GroEL to DnaK chaperone network behind the stability modulation of σ32 at physiological temperature in Escherichia coli. Issue 24 (9th November 2015) - Patra, Monobesh; Roy, Sourav Singha; Dasgupta, Rakhi; Basu, Tarakdas
Abstract : The stability of heat‐shock transcription factor σ 32 in Escherichia coli has long been known to be modulated only by its own transcribed chaperone DnaK. Very few reports suggest a role for another heat‐shock chaperone, GroEL, for maintenance of cellular σ 32 level. The present study demonstrates in vivo physical association between GroEL and σ 32 in E. coli at physiological temperature. This study further reveals that neither DnaK nor GroEL singly can modulate σ 32 stability in vivo; there is an ordered network between them, where GroEL acts upstream of DnaK. Abstract : Evidence for in vivo interaction between σ 32 and GroEL in E. coli . DnaK or GroEL alone cannot modulate σ 32 stability. For modulation of σ 32 stability, GroEL acts before DnaK.